Relationship of Competency of Community Health Nurse Coordinator (Perkesmas) and Level of Implementation of Perkesmas Activities at Public Health Center Work Area of Indramayu District Health Office - Nengsih Yulianingsih; Priyanto Priyanto; Nurohmat Nurohmat (Universitas Pendidikan Indonesia, 2022)
Community Health Nursing Service (Perkesmas) is one of the efforts of the puskesmas that supports the improvement of public health status by combining nursing knowledge/practice with public health through the support of active community participation. Perkesmas service activities can be carried out inside and outside the Puskesmas building. Inside the building, nurses provide nursing care for individuals who come to the puskesmas; in contrast, outside the building, nurses can give family nursing care and nursing care for special/health-prone groups in the Perkesmas target area. The purpose of this study was to determine the relationship between the competence of the Community Health Coordinator at the Public Health Center and the implementation of Community Health Activities in the work area of the Indramayu District Health Office. This research used a quantitative and analytical correlation approach with a cross-sectional design. The analysis was carried out in Public Health Centers throughout Indramayu Regency. The sample is 49 nurses appointed as health care coordinators at the Puskesmas. Data was collected through questionnaires, observation, and field supervision. The analysis results showed no relationship between the competence of puskesmas nurses and the level of implementation of health care activities. However, from the effects of partial hypothesis testing, it is known that there is a relationship between knowledge and training with the level of implementation of community health activities.This study recommends increasing the competence of nurses through increasing knowledge and training in hato optimize the implementation of the health care program.